A review of the development trend of adaptive cruise control for ecological driving. (August 2022) - Pan, Chaofeng; Huang, Aibao; Chen, Long; Cai, Yingfeng; Chen, Liao; Liang, Jun; Zhou, Weiqi
Adaptive cruise control (ACC) is an important part of the advanced driver assistance system (ADAS), which aims to improve the user's driving experience by reducing their manual operation and optimizing the vehicles' performance such as economy, comfort, and safety. With the gradual maturity of research on ACC, it presents various development trends. Among them, ecological adaptive cruise control (EACC) has great development potential in reducing emissions and improving driving range in internal combustion engine vehicles (ICEVs), hybrid electric vehicles (HEVs), and electric vehicles (EVs). This paper firstly reviews the components of classic ACC. Then the main design methods, research hotspots, and development trends of EACC for HEVs and EVs are introduced in detail. This paper not only provides a comprehensive analysis of EACC design and application in different type of vehicles but also forecasts the future research direction and trend, expecting to promote the further development of EACC efficiently.